Pengaruh Islamic Banking Service Quality dan Brand Islam terhadap Loyalitas Nasabah Bank Syariah di Indonesia - Auliana; Sissah; Sri Rahmah; Nurfitri Marthaliah (Scimadly Publishing, 2023)
The purpose of this study is to explain analyzing the influence of Islamic Banking Service Quality and Islamic Brand on customer loyalty at Bank Syariah Indonesia KCP Sarolangun. The type of research used in this research is quantitative research with a descriptive approach. The sample was used by Proportional Stratified Random Sampling. Methods of data collection using observation, questionnaires, and documents. Data analysis method using Multiple Regression Analysis. The results show that Islamic Banking Service Quality and Islamic Brand have a simultaneous effect on customer loyalty of Bank Syariah Indonesia KCP Sarolangun. Partially, Islamic Banking Service Quality and Islamic Brand also simultaneously affect customer loyalty of Bank Syariah Indonesia KCP Sarolangun. Adjusted R Value Square of 0.208 = 20.8% means that the independent variable jointly affects the dependent variable by 20.8% and the rest is influenced by other variables not included in the study.